2019
DOI: 10.1136/bmjopen-2018-023823
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional survey on job satisfaction and its associated factors among doctors in tertiary public hospitals in Shanghai, China

Abstract: ObjectivesDoctors in public hospitals in China face considerable pressure and excessive workloads, which are likely to predispose them to job dissatisfaction. We explored the job satisfaction of doctors and examined the influence of diverse sociodemographic characteristics.DesignThis was a cross-sectional study.SettingEleven tertiary public hospitals in Shanghai, China.ParticipantsThe questionnaire was designed based on the fifth National Health Service General Research, which was based on the Minnesota Satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 44 publications
4
23
0
1
Order By: Relevance
“…Job satisfaction is an intrinsic motivator of highly skilled health professionals. The positive link between job satisfaction and hospital performance revealed in this study is consistent with findings of previous studies [ 55 , 56 , 57 ]. Common strategies adopted by managers to improve job satisfaction include management and resource support, work-life balance, and teamwork.…”
Section: Discussionsupporting
confidence: 93%
“…Job satisfaction is an intrinsic motivator of highly skilled health professionals. The positive link between job satisfaction and hospital performance revealed in this study is consistent with findings of previous studies [ 55 , 56 , 57 ]. Common strategies adopted by managers to improve job satisfaction include management and resource support, work-life balance, and teamwork.…”
Section: Discussionsupporting
confidence: 93%
“…In China, tertiary hospitals are dedicated to providing medical care of patients with critical illness or complex diseases. Physicians in tertiary hospitals face more work stress than those in primary and secondary hospitals [ 19 ]. According to the Chinese Physician Practice Situation White Paper [ 20 ], the average working time for physicians in tertiary hospitals was 51 h per week (exceeding China’s legal limits of 40-h of work per week in China).…”
Section: Introductionmentioning
confidence: 99%
“…A study from Belgium reported that the practice environment is directly impacted by staff job satisfaction, intention to stay, and the perception of the quality of care 23 . Compared with Western countries, these aspects are not sufficiently enforced in China, especially job satisfaction, which is generally low in China 24,25 , as well as training 26 .…”
Section: Discussionmentioning
confidence: 99%